Determination of the elastic parameters of a material from a standardized dynamic stiffness testing. (10th November 2019) - Segovia-Eulogio, Enrique G.; Torres, Jennifer; Carbajo, Jesús; Ramis, Jaime; Arenas, Jorge P.
Abstract: Viscoelastic layers under floating floors are often used to reduce impact sound. A standardized dynamic stiffness test is routinely used to estimate the performance of a layer as an impact sound isolator. During the test, a material sample is placed between a load plate and a motionless rigid foundation. In this work, equations that provide a useful analytical description of the standardized test are derived. The new analytical approach is linked with the analysis of multilayer elastomeric bearings. The new approach leads to simpler analytical solutions as compared with those of previous studies, which makes them easy to translate into computer codes. The obtained expressions are almost independent of the shape of the boundary and are only dependent on static values such as the area and moments of inertia of the contour. Taking advantage of the new closed-form solutions, it is shown that, under certain restrictions, the analytical approach may be used to experimentally estimate the elastic parameters of a flexible material using a harmonic (frequency-dependent) analysis. It is reported that results obtained using the proposed approach are in good agreement with those obtained using a commercial finite element software. Highlights: A new analytical approach linked with multilayer elastomeric bearings is proposed. Derived equations provide a useful analytical description of a standardized test. The new approach leads to solutions that are easy to implement into computer codes. The approach can be used to estimate the elastic parameters of a flexible material.